Experimental investigation on onset of nucleate boiling and flow boiling heat transfer in a 5 × 5 rod bundle. (25th May 2022) - Li, Junlong; Zhang, Chaozhu; Zhang, Qi; Yang, Ping; Gan, Fujun; Chen, Shuo; Xiong, Zhenqin; Xiao, Yao; Gu, Hanyang
Highlights: Flow boiling heat transfer in a 5 × 5 rod bundle is experimentally studied. Increase in mass flux or pressure will decrease wall superheating at the ONB point. The effects of mass flux on subcooled and saturated boiling HTC are not distinct. The subcooled and saturated boiling HTC increase with pressure. The new ONB correlation and new saturated boiling correlation are established. Abstract: A flow boiling heat transfer experiment has been carried out in a square arranged 5 × 5 vertical rod bundle. The inlet pressure of the test section ranges from 3.5 to 7 MPa, mass flux varies from 250 to 500 kg/m 2 ·s, heat flux changes from 180 to 200 kW/m 2, and the vapor quality is lower than 0.25. The wall superheating degree data at the onset of nucleate boiling (ONB) point and the heat transfer data of both subcooled and saturated flow boiling regions are obtained. Parametric effects on wall superheating degree at ONB point and flow boiling heat transfer coefficient (HTC) are examined. For the present test conditions, an increase in mass flux or system pressure will decrease the wall superheating degree. The HTC in the subcooled and saturated boiling regions is not sensitive to the change of mass flux, while it increases in system pressure. The experimental data also have been compared with the existing empirical correlations. For the wall superheating degree, the existing ONB correlations are all significantly deviated from the experimental data, and a new ONB correlation is proposed to predict the experimental data. For the HTC in the subcooled boiling region, the Shah correlation provides good prediction accuracy for the current experimental data. For the HTC in the saturated boiling region, the selected correlations are all significantly deviated from the experimental data, and a new saturated boiling correlation that has a higher prediction accuracy for present data is established.